Penilaian Risiko Kesehatan Bahan Kimia pada Industri Pembuatan Alat Musik PT. XYZ Tahun 2024 - Febriana Maizura; Tejamaya, Mila (Jurnal Ilmiah Teknik Kimia, 2025)
The musical instrument manufacturing industry is an industry that has risks and dangers from using chemicals. The chemicals used include solvents and adhesives. Solvents are used as mixing and diluting materials for the wood painting process. Adhesives are used when connecting wooden parts to make a musical instrument. The solvents used are 1,2,4-trimethylbenzene, 2-butoxyethanol, 2-ethoxyethyl acetate, 4-methylpentan-2-one, cumene, cyclohexanone, ethyl acetate, ethyl benzene, mesitylene, naphthalene, n-butyl acetate, solvent naphtha (petroleum), toluene, and xylene. The assessment of chemical health risks refers to the Chemical Health Risk Assessment (CHRA) DOSH Malaysia in 2018. This study is qualitative because the determination of the level of hazard, exposure, and evaluation are carried out qualitatively. Data collection begins with chemical identification, then conducting observations and interviews, followed by health risk assessment, adequacy of control, and determination of action priorities for each inhalation and dermal exposure. The results of the study at PT. XYZ for inhalation exposure obtained a Risk Rating value of 6 (moderate) to 16 (high), while for dermal exposure the value was moderate 1, moderate 2, and high 1. The coloring process with paint has an action priority of 3 while the washcoat, wapping, and logo installation processes have an action priority of 2 which requires improvement of existing risk control.